Enhanced expression of miR-889 forecasts an unfavorable prognosis and facilitates cell progression in hepatocellular carcinoma - He Wang; Huiwen Wang; Wenyu Cui; Qiao Zhang; Jing Li; Qi Zhang (BMC, 2021)
Abstract Background As a new type of molecular marker, microRNAs (miRNAs) can be used for early diagnosis and prognosis prediction of malignant tumors, and has broad clinical application prospects. This paper mainly studies the important role of miR-889 in the occurrence and development of hepatocellular carcinoma and the prognostic significance of miR-889 in hepatocellular carcinoma. Methods Quantitative real-time PCR analysis detected the expression levels of miR-889 in hepatocellular carcinoma tissues and cell lines. Kaplan-Meier curve and Cox regression analysis were used to explore the prognostic significance of miR-889 in hepatocellular carcinoma. The CCK-8 and Transwell assays assay were used to assess cell proliferation, migration, and invasion abilities ability. Results The expression of miR-889 in hepatocellular carcinoma tissues was significantly higher than that in adjacent tissues. Overexpression of miR-889 was significantly associated with TNM stage, hepatitis B virus infection, and cirrhosis. Patients with high miR-889 expression had shorter overall survival than those with low miR-889 expression. And functional studies in two hepatocellular carcinoma cell lines have shown that overexpression of miR-889 significantly promoted cell proliferation, migration, and invasion in vitro. Conclusions Overall, miR-889 was upregulated in hepatocellular carcinoma tissues and cell lines, and overexpression of miR-889 promoted cell proliferation, migration, and invasion in hepatocellular carcinoma cells. Based on our findings, high expression of miR-889 may promote the progression of hepatocellular carcinoma, and high expression of miR-889 is also forecasted for an unfavorable prognosis in hepatocellular carcinoma.